Zinc deficiency and school-age childrenâs memories - Indria Laksmi Gamayanti, Setianingsih, Djaswadi Dasuki, (Universitas Gadjah Mada, 2014)
Zinc deficiency is associated with cognitive and motor delay in children. Moreover, it is associatedwith deficits in activity and attention in nutritional deficiency children. This study was conductedto evaluate the correlation between zinc deficiency with memory of children. A cross sectionalstudy design was employed from June 1st to 30th, 2013 among school-age children in KlatenDistrict, Central Java who met inclusion and exclusion criteria. Sixty five eligible children wereassessed their health, socio-economic and nutritional status. Hemoglobin levels were measuredby the standart cyanoblue method. Plasma zinc levels were analyzed with flame atomic absorptionspectrophotometry (AAS). Short-term memory (STM) was measured using the instrument WechslerIntellegence Scale for Children (WISC0 subtest Digit Span Memory Test and long term memory(LTM) was assessed using the recall of narrative. Independent t-test was used to compare theSTM or LTM between groups of each independent factors. Linear regression analysis was usedto determine the independent factors associated with the STM or LTM. The STM scores of thechildren with zinc deficiency (6.1 Â± 1.3) was significantly higher than those with normal zinclevel (10.7 Â± 3.1) [p=0.0004; 95%CI= -6.98 â (-2.14)]. However, the LTM for both group ofthe children were not significantly different (p=0.658; 95%CI= -3.16 â 2.01). A significantcorrelations between zinc levels, hemoglobin level and socio-economic status with the STM scoreswere observed (p<0.05), whereas nutritional status was not (p>0.05). In contrast, no significantcorrelations between zinc levels, hemoglobin levels, socio-economic status, nutritional status andthe LTM scores was observed in the school age children (p>0.05). In conclusion, zinc deficiency isassociated with STM loss in the school age children, however it is not associated with LTM loss.Moreover, hemoglobin level and socio-economic status are found to be independent factors forSTM loss, however they are not independent factors for LTM loss.